Mga Is Sufficient To Activate Transcription In Vitro of sof-sfbX and Other Mga-Regulated Virulence Genes in the Group A Streptococcus - Almengor, Audry C. (American Society for Microbiology, 2006)
The group A streptococcus (GAS), or Streptococcus pyogenes, is a strict human pathogen of medical significance, causing infections ranging from pharyngitis (strep throat) to necrotizing fasciitis (flesh-eating disease). Several virulence genes that encode factors important for colonization, internalization, and immune evasion are under the control of the multiple gene regulator of the GAS, or Mga. Mga functions as a DNA-binding protein that interacts with sites both proximal (Pemm and PscpA) and distal (PsclA) to the start of transcription for the genes that it regulates. The genes encoding serum opacity factor, sof, and a novel fibronectin-binding protein, sfbX, are cotranscribed and represent two uncharacterized Mga-regulated virulence genes in the GAS. Analysis of the promoter region of sof-sfbX identified a putative Mga-binding site 278 bp upstream of the regulated start of transcription as determined by primer extension. Electrophoretic mobility shift assays demonstrated that Mga is able to bind specifically to the single distal site in a fashion similar to the previously characterized PsclA. In order to better understand the events that take place at this and other Mga-regulated promoters, an in vitro transcription assay was established. Using this assay, we showed that Mga is sufficient to activate transcription in vitro for Mga-regulated promoters containing both proximal (Pemm) and distal (PsclA and Psof-sfbX) binding sites. These results indicate that additional factors are not required for Mga-specific activation at diverse promoters in vitro, although they do not rule out the potential influence of other components on the Mga virulence regulon in vivo.